2018
DOI: 10.1097/ncq.0000000000000301
|View full text |Cite
|
Sign up to set email alerts
|

The Johns Hopkins Fall Risk Assessment Tool

Abstract: Patient falls and fall-related injury remain a safety concern. The Johns Hopkins Fall Risk Assessment Tool (JHFRAT) was developed to facilitate early detection of risk for anticipated physiologic falls in adult inpatients. Psychometric properties in acute care settings have not yet been fully established; this study sought to fill that gap. Results indicate that the JHFRAT is reliable, with high sensitivity and negative predictive validity. Specificity and positive predictive validity were lower than expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 15 publications
1
51
0
4
Order By: Relevance
“…The resulting tool (SFRST) is provided in Table S3. In line with other FRSTs (Poe, Cvach, Dawson, Straus, & Hill, ; Rosario et al., ) and conclusions drawn by Latt et al. (), when using the SFRST patients with no ability to fall (such as, patients with extremely severe motor impairment or in a minimally responsive state) should be given a low risk score; this will reduce false positives and improve accuracy.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The resulting tool (SFRST) is provided in Table S3. In line with other FRSTs (Poe, Cvach, Dawson, Straus, & Hill, ; Rosario et al., ) and conclusions drawn by Latt et al. (), when using the SFRST patients with no ability to fall (such as, patients with extremely severe motor impairment or in a minimally responsive state) should be given a low risk score; this will reduce false positives and improve accuracy.…”
Section: Discussionsupporting
confidence: 62%
“…Including impulsive behaviour, it has been suggested that patient behaviour contributes to the majority of falls in rehabilitation (Thomas et al., ). Impulsive behaviour has previously been (i) identified as contributing to falls in patients with brain injury (Breisinger & Campbell, ; Carmine, Murphy, Ambush‐Mansfield, & Robinson, ; Rapport et al., ) and (ii) included in two FRSTs developed in rehabilitation (Breisinger & Campbell, ; Ruroede et al., ) and three developed in acute care settings (Barker et al., ; Hendrich, Bender, & Nyhuis, ; Poe et al., ). Finally, all five items in the SFRST were identified as contributing to falls in one or more of the studies undertaken prior to this current study (McKechnie et al., , ,b, ), which supports their clinical relevance in the prediction of falls.…”
Section: Discussionmentioning
confidence: 99%
“…However, many including ABCS injurious fall screening tool,13 CAREFALL,14 HOME FAST,15 Hendrich II Fall Risk Model,16 STRATIFY,17 University of Pittsburgh Medical Center screening tool,18 New York–Presbyterian Fall and Injury Risk Assessment Tool,18 19 Johns Hopkins Fall Risk Assessment Tool,20 Maine Medical Center Fall Risk Assessment,19 Morse Fall Scale19 21 and Spartanburg Fall Risk Assessment Tool22 have not been assessed in the ED setting. The ED represents a unique clinical environment and risk screening may assist with identifying patient’s risk factors, providing evidence of assessment and prompt intervention.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] Patients were eligible for inclusion in this study if their risk score on admission was 6 or greater. Patients were excluded if they had a diagnosis of dementia, could not clearly remember the past year, could not sit on the edge of the bed, or were unable to participate in a verbal evaluation.…”
Section: Patientsmentioning
confidence: 99%
“…These floors did not include patients admitted to the oncology, cardiology, neurology, psychiatry, physical medicine and rehabilitation, or surgery services. All consecutively admitted patients aged 18 to 70 years, who were English speaking, able to follow verbal commands, ambulatory, and deemed at moderate or high risk for falling, were eligible for inclusion.Risk of falling was assessed using the Johns Hopkins Fall Risk Assessment score 13,14 ; a score of less than 6 is considered low risk, 6 to 13 is considered moderate risk, and greater than 13 is considered high risk. [13][14][15] Patients were eligible for inclusion in this study if their risk score on admission was 6 or greater.…”
mentioning
confidence: 99%